Analisa Penyebab tidak Terkirimnya Data Radar Cengkareng(CKG)3 dari Jakarta Air Traffic Service Center (JATSC) ke AirNav Cabang Halim Perdanakusuma - Muhammad Caesar Akbar; Bongot Hotmarojahan Sinaga (Politeknik Penerbangan Makassar, 2022)
Perum Indonesian Aviation Navigation Service Provider (LPPNPI) or AirNav Indonesia was established in accordance with the mandate of Law no. 1 of 2009 concerning Aviation and Government Regulation (PP) Number 77 of 2012 concerning Perum LPPNPI. Perum LPPNPI is the only provider of flight navigation in Indonesia which was previously handled by PT Angkasa Pura I (Persero) and PT Angkasa Pura II (Persero) and the Ministry of Transportation which manages UPT for airports throughout Indonesia. AirNav Indonesia is divided into 2 airspaces based on the Flight Information Region (FIR), namely the Jakarta FIR, which is important at the Jakarta Air Traffic Service Center (JATSC) Branch Office and the Ujung Pandang FIR, which must be at the Makassar Air Traffic Service Center (MATSC) Branch Office. Center (JATSC) Air Navigation Indonesia is a business entity that provides flight navigation services in Indonesia which is located at Soekarno - Hatta Airport and does not aim to seek profit, in the form of a State-Owned Enterprise whose entire capital is owned in the form of separate State assets and is not divided into shares in accordance with Law Number 19 of 2003 concerning StateOwned Enterprises. One of the units of the Aviation Automation Facilities division at the Jakarta Air Traffic Services Center (JATSC) is the Automatic Message Switching System – Aeronautical Data Processing System (AMSS-ADPS) unit. AMSS - ADPS Unit is a work unit that maintains and prepares equipment conditions related to message handling and aeronautical data processing to assist flight safety at JATSC. The Automatic Message Switching System – Aeronautical Data Processing System (AMSS –ADPS) unit owns and maintains equipment including the ATS Message Handling System (AMHS), Aeronautical Data Processing System (ADPS), Web Server, E – Charting, Automatic Terminal Information Service ( ATIS). ), Converter, Notam Office (NOF) and other Automation Facilities are Unit Flight Data Processing System – Radar Data Processing System (FDPS-RDPS). This unit maintains and operates equipment such as the Enhanced Jakarta Automated Air Traffic Control System (EJAATS), Jakarta Automate Air Traffic Services (JAATS), Controller Pilot Data Link Communication (CPDLC), and Automatic Surface Movement and Guidance Control System (ASMGCS).